Antimicrobial Resistance Profiles of Salmonella spp. Isolated from Swine Feces in Phayao Province, Thailand - Boonkerd, Nitsara; Chaikhiandee, Surasak (Journal of Food Health and Bioenvironmental Science, 2023)
Antimicrobial resistance in Salmonella spp. is a serious issue for food safety. In Thailand, antibiotics are being used more frequently for both prophylaxis and treatment as commercial swine farming expands. Antimicrobial resistance has been generated as a result of the widespread use of antimicrobials in animal agriculture. For this study, we examined the antimicrobial resistance profiles and resistance percentages of Salmonella spp., which were isolated from swine fecal samples in Phayao province. The results showed that the overall prevalence of Salmonella spp. in the fecal samples in Phayao Province was 49.17%. The highest prevalence of Salmonella spp. contamination was found in the piglet fecal samples (70%), followed by sick swine fecal samples (65%) and adult swine fecal samples (40%). The recovered 100 Salmonella spp. isolated from adult swine, sick swine and piglet feces were 34, 22 and 44 respectively. After that all isolates were tested for antimicrobial susceptibility. It was found that the highest resistance rate to ampicillin, which were equal to 79.41, 81.82 and 95.45 % in isolates from adult swine, sick swine, and piglets, respectively. Salmonella spp. isolates were resistant to ampicillin (87%), trimethoprim-sulfamethoxazole (84%), tetracycline (62%) and chloramphenicol (61%). Interestingly, Salmonella spp. isolated from piglets had highest percentage of resistance. Salmonella spp. isolated were resistant to ampicillin, trimethoprim-sulfamethoxazole, tetracycline, chloramphenicol, and cefotaxime which were equal to 95.45, 95.45, 90.91, 56.82 and 52.27%, respectively. MDR Salmonella was observed among 87 of 100 (87%) isolates. Whereas seventeen different multidrug-resistant profiles were observed. The most frequently found antimicrobial resistance profiles was AMP-SXT-TE-CIP. Furthermore, the probability of resistance to antimicrobial agents has increased. Further description of the associations between resistance and how resistance spreads within farms, are required before effective intervention strategies can be designed to control MDR Salmonella in swine.